Iterative image reconstruction algorithms in coronary CT angiography improve the detection of lipid-core plaque - a comparison with histology - Puchner, Stefan B.; Ferencik, Maros; Maurovich-Horvat, Pal; Nakano, Masataka; Otsuka, Fumiyuki; Kauczor, Hans-Ulrich; Virmani, Renu; Hoffmann, Udo; Schlett, Christopher L. (European radiology, 2015)
To evaluate whether iterative reconstruction algorithms improve the diagnostic accuracy of coronary CT angiography (CCTA) for detection of lipid-core plaque (LCP) compared to histology.
Published online: 3 September 2014
Gesehen am 16.07.2020